Supported Decision-Making in Persons With Dementia: Development of an Enhanced Consent Procedure for Lumbar Puncture - Wied, Theresa S.; Haberstroh, Julia; Gather, Jakov; Karakaya, Tarik; Oswald, Frank; Qubad, Mishal; Scholten, Matthé; Vollmann, Jochen; Pantel, Johannes; , The ENSURE Consortium; Haberstroh, Julia; Oswald, Frank; et al. (Frontiers in Psychiatry, 2021)
The right to make autonomous decisions is enshrined in law. However, the question how persons with cognitive deficits can be enabled to make autonomous decisions has not been satisfactorily addressed. In particular, the concept of supported decision-making and its implementation into practice has been poorly explored for persons with dementia (PwD).This article describes the empirical development and implementation of support tools to enhance informed consent processes (so called enhanced consent procedures/ECP) for PwD on whether to undergo lumbar puncture. In the end of the process of pilot testing and further development of the tools, the following tools were defined: (1) Standardized Interview Structure, (2) Elaborated Plain Language, (3) Ambience and Room Design, (4) Keyword Lists, (5) Priority Cards, (6) Visualization, and (7) Simplified Written Informed Consent (Patient Information), as well as the general attitude (8) Person-Centered Attitude of the facilitator. As the development, implementation and evaluation of ECP tools is one objective of the transnational ENSURE project, we also include an overview of future empirical procedures. So far, our findings can serve as a selection of possibilities to support PwD in decision-making and help practitioners achieve an appropriate balance between the autonomy and protection of PwD in complex decision-making situation. Future studies should address the question if the proposed set of tools is effective to enhance informed consent processes in PwD.